Multiple domains of social support are associated with diabetes self-management among Veterans. (December 2019) - Gray, Kristen E; Hoerster, Katherine D; Reiber, Gayle E; Bastian, Lori A; Nelson, Karin M
Objectives: To examine, among Veterans, relationships of general social support and diabetes-specific social support for physical activity and healthy eating with diabetes self-management behaviors. Methods: Patients from VA Puget Sound, Seattle completed a cross-sectional survey in 2012–2013 ( N = 717). We measured (a) general social support and (b) diabetes-specific social support for healthy eating and physical activity with domains reflecting support person participation, encouragement, and sharing ideas. Among 189 self-reporting diabetes patients, we fit linear and modified Poisson regression models estimating associations of social support with diabetes self-management behaviors: adherence to general and diabetes-specific diets and blood glucose monitoring (days/week); physical activity (< vs. ≥150 min/week); and smoking status (smoker/non-smoker). Results: General social support was not associated with diabetes self-management. For diabetes-specific social support, higher healthy eating support scores across all domains were associated with better adherence to general and diabetes-specific diets. Higher physical activity support scores were positively associated with ≥150 min/week of physical activity only for the participation domain. Discussion: Diabetes-specific social support was a stronger and more consistent correlate of improved self-management than general social support, particularly for lifestyle behaviors. Incorporating family/friends into Veterans' diabetes self-management routines may lead to better self-management and improvements in disease control and outcomes.